2020
DOI: 10.1117/1.jmi.8.s1.014501
|View full text |Cite
|
Sign up to set email alerts
|

Cascaded deep transfer learning on thoracic CT in COVID-19 patients treated with steroids

Abstract: . Purpose: Given the recent COVID-19 pandemic and its stress on global medical resources, presented here is the development of a machine intelligent method for thoracic computed tomography (CT) to inform management of patients on steroid treatment. Approach: Transfer learning has demonstrated strong performance when applied to medical imaging, particularly when only limited data are available. A cascaded transfer learning approach extracted quantitative features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“… 95 A severity score derived from lung images can be used for triaging the patient to decide home discharge, regular hospital admission, or intensive care unit admission. 96 The imaging characteristics can be used for prognosis assessment 97 and evaluation of the extent of disease, 11 and it has potential to predict the length of hospital stay. 98 …”
Section: Ai Using Clinical Histopathology and Genomics With Imaging Datamentioning
confidence: 99%
See 2 more Smart Citations
“… 95 A severity score derived from lung images can be used for triaging the patient to decide home discharge, regular hospital admission, or intensive care unit admission. 96 The imaging characteristics can be used for prognosis assessment 97 and evaluation of the extent of disease, 11 and it has potential to predict the length of hospital stay. 98 …”
Section: Ai Using Clinical Histopathology and Genomics With Imaging Datamentioning
confidence: 99%
“…The temporal changes can be used to monitor the patients’ response to the treatment and to inform the decision for discharge. 97 Lung ultrasound has also been suggested as the imaging tool for COVID-19 pandemic in disease triage, diagnosis, prognosis, severity assessment, and monitoring the treatment response. 13 …”
Section: Ai Using Clinical Histopathology and Genomics With Imaging Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In our preliminary study, we found that quantitative parameters of QCT may serve as a useful endpoint in evaluating treatment e cacy in patients with COVID-19 [13]. Further, we found that patients with severe COVID-19 receiving steroid therapy showed a signi cant different recovery pattern compared to those not receiving steroid therapy using a deep learning method [14]. However, due to the black-box brought by deep networks, we were not able to further interpret the difference we have observed.…”
Section: Discussionmentioning
confidence: 89%
“…This may be particularly valuable in circumstance of minor effect as new therapies are developed and evaluated [7] .We hypothesize that QCT can serve as a tool for monitoring steroid treatment response during the course of disease. Our preliminary studies have con rmed the value of QCT in monitoring the progression and clinical decision-making in patients with 14]. However, the effect of steroids on quantitative chest CT parameters during the treatment process remains unknown.…”
mentioning
confidence: 73%